Large‐Scale Channel Response to Erosion‐Control Measures - C. Ylla Arbós; A. Blom; S. R. White; R. Patzwahl; R. M. J. Schielen (Water Resources Research)
Abstract Erosion‐control measures in rivers aim to provide sufficient navigation width, reduce local erosion, or to protect neighboring communities from flooding. These measures are typically devised to solve a local problem. However, local channel modifications trigger a large‐scale channel response in the form of migrating bed level and sediment sorting waves. Our objective is to investigate the large‐scale channel response to such measures. We consider the lower Rhine River from Bonn (Germany) to Gorinchem (the Netherlands), where numerous erosion‐control measures have been implemented since the 1980s. We analyze measured bed level data (1999–2020) around four erosion‐control measures, comprising scour filling, bendway weirs, and two fixed beds. To get further insight on the physics behind the observed behavior, we set up an idealized one‐dimensional numerical model. Finally, we study how the geometry and spacing of the measures affect channel response. We show that erosion‐control measures reduce the sediment flux due to (a) lack of erosion over the measure and (b) sediment trapping upstream of the measure, resulting in downstream‐migrating incision waves that travel tens of kilometers at decadal timescales. When the measures are in close proximity, their downstream effects may be amplified. We conclude that, despite fulfilling erosion‐control goals at the local scale, erosion‐control measures may worsen large‐scale channel‐bed incision.